Measuring the service reliability and the passenger experience in frequence-based transport systems: Artikel - Cerreto, Fabrizio (Proceedings from the Annual Transport Conference at Aalborg University, 2024)
This article explores the application and limitations of operational Key Performance Indicators (KPI) in frequency-based metro systems, specifically focusing on the Copenhagen Metro and Greater Copenhagen Light Rail. Recognizing that currently used KPIs, which primarily measure the frequency of station departures, fails to capture crucial aspects such as travel time reliability and system responsiveness during disruptions, the study proposes a reevaluation of the assessment focus. It delves into alternative measures that consider both the reliability of departures and the quality of the passenger experience. The research methodology evaluates metro performance through a variety of new KPIs, emphasizing time metrics like deviation and stability, thereby providing a more nuanced understanding of service reliability. This preliminary exploration seeks not only to enhance operational assessments but also to aid strategic planning and the execution of improvements within high-frequency public transportation systems. The article underscores the need for more adaptive, comprehensive KPIs that reflect the true operational realities of metro systems, suggesting that such advancements could significantly improve passenger satisfaction and system efficiency.